Refinement of chromosome 3p22.3 region and identification of a susceptibility gene for bipolar affective disorder1. Issue 2 (31st December 2012) - Secolin, Rodrigo; Banzato, Claudio E.M.; Mella, Lucas F.B.; Santos, Marilza L.; Dalgalarrondo, Paulo; Lopes‐Cendes, Iscia
Abstract Genome‐wide association studies and meta‐analysis, as well as our own previous family‐based association results, have pointed to chromosome (ch) 3p22.3 and 3p21.1 as candidate regions to contain a susceptibility gene for bipolar affective disorder (BPAD). In the present study, we further refined the region of interest on ch 3p22.3. We genotyped 94 SNPs within the candidate region in 74 families and performed family‐based association analysis using a transmission disequilibrium test. One single SNP (rs166508) was associated with the BPAD phenotype (P = 0.0187). This SNP is located within intron 15 of the integrin alpha 9 (ITGA9) gene. ITGA9 encodes the α9 subunit of the α9β1 integrin, a membrane glycoprotein receptor for neurotrophins, such as nerve growth factor (NGF) and brain‐derived neurotrophic factor (BDNF). Quantification of ITGA9 transcripts in the peripheral blood of patients with BPAD and controls showed an upregulation of ITGA9 (Kruskal–Wallis P = 0.0339) in patients with the disease‐associated genotype (rs166508*A/A), compared to those with rs166508*G/G and rs166508*G/A genotypes. Sequencing of the ITGA9 cDNA revealed a sequence variant (r.1689_1839del) in rs166508*A carriers, which leads to loss of the entire exon 16. In silico analysis revealed that the deleted region contains three putative microRNA binding sites, which may be involved in the negative regulation of ITGA9. In conclusion, our results confirm previous evidence pointing to a candidate region for BPAD on ch 3p.22.3. In addition, we suggest a molecular substrate that could explain the increase of ITGA9 mRNA levels in probands with BPAD, proposing a new mechanism that could be involved in the genetic susceptibility to the disease. © 2012 Wiley Periodicals, Inc.